2022
DOI: 10.1039/d2tb01351g
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing cancer cells from normal cells with an organelle-targeted fluorescent marker

Abstract: This paper reported a hemicyanine dye was used for distinguish cancer cells from normal cells by their different organelles targetability. Probe 1, a red emission hemicyanine functional dye, was connected...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Thus, three bromine-containing fluorophores including 7bromo-2H-chromen-2-one, 6-bromo-2-methyl-1Hbenzo[de]isoquinoline-1,3(2H)-dione and 9-bromo-5Hbenzo[a]phenoxazin-5-one were grafted with 1-adamantanyl methanamine via nucleophilic aromatic substitution reaction under palladium-catalyzed and then dyes Coum-Ad, NP-Ad, NR-Ad were obtained with isolated yields of 11.9 %, 42.0 % and 21.7 %, respectively. The characterization (containing 1 H NMR, 13 C NMR, FTIR and HRMS(ESI + )) of Coum-Ad, NP-Ad and NR-Ad were recorded in the Supporting Information for details.…”
Section: Design and Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, three bromine-containing fluorophores including 7bromo-2H-chromen-2-one, 6-bromo-2-methyl-1Hbenzo[de]isoquinoline-1,3(2H)-dione and 9-bromo-5Hbenzo[a]phenoxazin-5-one were grafted with 1-adamantanyl methanamine via nucleophilic aromatic substitution reaction under palladium-catalyzed and then dyes Coum-Ad, NP-Ad, NR-Ad were obtained with isolated yields of 11.9 %, 42.0 % and 21.7 %, respectively. The characterization (containing 1 H NMR, 13 C NMR, FTIR and HRMS(ESI + )) of Coum-Ad, NP-Ad and NR-Ad were recorded in the Supporting Information for details.…”
Section: Design and Preparationmentioning
confidence: 99%
“…For example, previous study reported a hemicyanine dye that could complex with β‐CD in aqueous solution. However, when the fluorescence quantum yield of this dye in aqueous solution was increased from 1.57 % to 13.1 %, the amount of β‐CD was over 700 times than that of the dye due to low inclusion equilibrium constant (398 M −1 ) [13] . The inclusion equilibrium constants of fluorophores and CDs generally ranged from 10 M −1 to 10 3 M −1 (Table S1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18–21 Nevertheless, many admirable anticancer drugs are available, but with no bioimaging ability, 22,23 while numerous bioimaging agents are known without anticancer properties. 24 Hence, the discovery of an anticancer agent with bioimaging ability is a looming challenge but a surging need of the time. 25…”
Section: Introductionmentioning
confidence: 99%
“…8 A low host–guest complexation constant leads to an increase in the demand for β-CDs in the application of biological imaging (>800 eq. ), 9 which may have an abnormal impact on the cellular microenvironment. 10 The structural similarity between adamantane (Ad) and the hydrophobic cavity of β-CDs enables the formation of host–guest complexes with a binding constant in the range of 10 3 –10 4 M −1 at a 1 : 1 stoichiometry, which greatly improves the thorny problem of excessive β-CD dosage.…”
Section: Introductionmentioning
confidence: 99%